Pertanggung Jawaban Notaris Terhadap Keabsahan Akta Outentik Yang Dilakukan Secara Electronic Dalam Pembuktian Di Pengadilan - Dendik Surya Wardana; Iswi Hariyani; Dodik Prihatin AN (Jurnal Ilmu Kenotariatan, 2021)
The notary's responsibility for the notary's deed based on electronic transactions, including the protection of electronic information confidentiality relating to network networks in the electronic exchange of information.The notary's role in proving criminal matters against the deed he performs is limited to acting as an expert witness to justify what was seen or witnessed and what was not seen or witnessed. what was conveyed at the time the deed was drawn up The status of a notary deed in the form of a digital or cybernotary is covered by Article 187 of the Criminal Procedure Code, which governs the type of evidence. Since the Electronic System in a multiplication speaker produces information that can no longer be separated from him. To put it another way, their presence should be equivalent to or identical to written proof, such as a document, a forged deed, or an authentic deed. The power of digital proof of a Notary deed can be equated to that of an authentic deed if its authenticity is objectively assured, it can justify who the legal subject is responsible, and the electronic system is guaranteed to function properly (accredited). As long as the parties cannot demonstrate otherwise, the system's declarations may be considered theoretically and legally valid. KEYWORDS : Notary, Electronic Deed, Proof.